2021
DOI: 10.1108/nfs-05-2021-0156
|View full text |Cite
|
Sign up to set email alerts
|

Screen time-based sedentary behaviour, eating regulation and weight status of university students during the COVID-19 lockdown

Abstract: Purpose This study aims to investigate the relationships among screen time-based sedentary behaviour, eating self-regulatory skills and weight status among private university students during the Movement Control Order (MCO). Design/methodology/approach A total of 186 private university students was enrolled in this cross-sectional study using a combination of snowball and purposive sampling approaches. Anthropometric measurements, including body height, body weight before and during the MCO enforcement were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…Students that live with their family members have a high tendency to consume home-cooked meals rather than dining in at restaurants [ 23 ]. In Malaysia, the COVID-19 outbreak resulted in the transition of the physical lectures in universities into virtual lectures [ 24 , 25 ]. Hence, many undergraduates may have returned to their homes and stayed with their family members.…”
Section: Discussionmentioning
confidence: 99%
“…Students that live with their family members have a high tendency to consume home-cooked meals rather than dining in at restaurants [ 23 ]. In Malaysia, the COVID-19 outbreak resulted in the transition of the physical lectures in universities into virtual lectures [ 24 , 25 ]. Hence, many undergraduates may have returned to their homes and stayed with their family members.…”
Section: Discussionmentioning
confidence: 99%
“…In outcomes that measured gaming, 50% (1/2) of univariate correlations were statistically significant. The significant association was a negative correlation between the use of gaming consoles and self-regulation around eating (r= À0¢15; p = 0¢04), 62 and the non-significant association was 'gaming on a computer' and self-regulation around eating (r= À0¢06; p=NR). 62 Regarding cell phone use, 17% (1/6) of outcomes yielded significant associations, with increases in cell phone use being significantly associated with the consumption of sweetened foods (OR=1¢78 95%CI 1¢18 −2¢67).…”
Section: Associations Between Screen Time and Multiple Correlatesmentioning
confidence: 98%
“…Diet and smoking. Three studies 7,8,62 (yielding 29 independent outcomes) reported correlates in relation to diet and smoking, of which 35% (10/29) were statistically significant.…”
Section: Associations Between Screen Time and Multiple Correlatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that people with obesity are at increased risk of severe COVID-19 symptoms (Stefan et al , 2020; Finer et al , 2020). It is clear that eating habits and lifestyle have changed during COVID-19 lockdown (Di Renzo et al , 2020; Mohajeri et al , 2021; Tan et al , 2021a; Tan et al , 2021b) and in the midst of economic crisis in Lebanon. Nutrition is becoming an important issue because malnutrition, including obesity and nutrients deficiency, influence the COVID-19 patients’ outcomes; therefore, healthy nutritional status must be maintained by following a healthy diet (Butler and Barrientos, 2020; Hendren et al , 2021).…”
Section: Introductionmentioning
confidence: 99%